Aspergillus Proteolitik Indigenous dari Koji dan Kemampuannya Mendegradasi Aflatoksin B1 - Sardjono Sardjono; Endang Sri Rahayu; Sri Raharjo; Kapti Rahayu Kuswanto (agriTECH, 2004)
Legume and cereals are always exposed to the danger of fungal contamination. Among such fungi, some species of the genus Aspergillus are potential of aflatoxins producer. Aflatoxin BI (AFB1) which is the most carcinogenic mycotoxins , known very stable under cooking condition and other processing factors. The removal of AFB1 by degradation or detoxification is critical to reduce risk to human health. Microbiological degradation is a promising method for AFB1 degradation compared to others. The aim of this research was to isolate the proteolytic Aspergillus strain from "koji" and to determine its ability to degrade AFB). Out of 18 strains of Aspergillus, 16 strains were found proteolytic and only 5 strains had no afiatoxigenic properties, but all of them were able to degrade AFB1. There were no spesific pattern of the rate of AFBI degradation. Strain of KKB4 was identified as Aspergillus oryzae, that possess the highest ability to degrade AFB1. Two kind of substances were formed after degradation which were more polar than AFB1. The rate of AFB) uptake by Aspergillus oryzae KKB4 was similar with that of mycelia! growth. Aflatoxin BI inhibits mycelium growth, vesicle and conidial head formation.